Efektivitas Rezim Arms Trade Treaty (ATT) Dalam Mengurangi Penyebaran Senjata Ilegal - Adinia Nuraini; Siven Trigveli Tambolang; Annisa Rahmatin; Lailatul Badrian; Pia Dewi Rahma (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The illegal arms trade is a serious threat to global stability and human security. These practices not only exacerbate armed conflicts and violence, but also threaten the national security of various countries, create regional instability, and increase the risk of terrorism and transnational crime. To respond to this challenge, the Arms Trade Treaty (ATT) was introduced in 2014 as an effort by the international community to combat the illegal arms trade. The ATT aims to regulate the international trade in conventional arms, prevent and eliminate illegal arms transfers, and ensure that the arms trade is conducted responsibly and transparently. This paper aims to evaluate the effectiveness of the ATT regime in reducing the spread of illegal weapons globally by analyzing the impact of ATT implementation on the flow of illegal weapons. The research design used for this paper is a desk research method with journal reading sources and websites (online). We use the theory of Compliance Regime Effectiveness and the concept of Ex-Post Facto to analyze. The results show that the ATT has contributed to strengthening the regulation of the arms trade through increased transparency and accountability among member states.